Development of Student Worksheets Based Computational Thinking for Derivatives of Algebra Function - Kurniasi, Eka Rachma; Vebrian, Rajab; Arsisari, Ayen (Universitas Muhammadiyah Mataram, 2022)
Computational Thinking (CT) is one of the important thinking skills in the 21st century. However, mathematics has not been widely developed in the classroom learning process. The results of the initial study show that there is no student worksheet based on compuational thinking for high school students. This study aims to develop a Student Worksheet (LKPD) based on Computational Thinking the derivatives of algebra function of for high school students. This type of research is development research with ADDIE model development research design. The steps are analysis, design, development, implementation, and evaluation. The research subjects were high school students of grade 11 who received material on the derivatives of algebraic functions. The research instruments were student worksheet as a development product, expert validation questionnaires, teacher practicality questionnaires, and student response questionnaires. The product developed in this study is a CT-based math worksheet for the derivatives of algebraic functions for high school students. This product is validated by material experts and mathematics learning experts. Furthermore, the practitioner test by high school mathematics teachers and questionnaire responses by high school students, the number of students are 20 people. The results of this study are the Mathematics Student Worksheets based on Computational Thinking material for the derivatives of algebra fuction for high school students that are valid and practical. The resulting LKPD contains CT steps, namely abstraction, generalization, decomposition, algorithmic, debugging. This worksheet is one way to integrate computational thinking in mathematics learning.